Hidup dalam Stigma: Kekerasan dan Religiuitas Bejingan - Asma Wati; Sholih Muadi; George Towar Ikbal Tawakkal (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
The purpose of this study is to find out that violence and religiosity can actually run side by side where both are able to make the figure of Bejingan have a different social strata from other communities. Violence is a characteristic of Bejingan in resolving conflicts in society while religiosity as a culture that has become ingrained in the community. To provide an understanding of the life of Bejingan in the community, this article explores how Bejingan lives in a standard of violence that has become a distinctive feature and cultural religiosity adopted in the community of Pamekasan Madura Regency. the method used in this study is qualitative with a case study approach where the researcher reveals in depth related to the life of Bejingan in Pamekasan Regency. The results obtained from this research are that Bejingan has long lived in stikma where its existence is always associated with violence and crime, whereas furthermore the role of Bejingan in the sphere of society has many benefits and benefits where security, conflict between citizens and the welfare of the community are influenced by the figure of Bejingan. Furthermore, the Bejong lives in a balanced balance of religiosity and violence where life is influenced by good relations between gods by practicing worship while still maintaining self-esteem in the distinctive characteristics of the heroism possessed. The scientific contribution of this article discusses the extension of the lives of local figures who have conflicting but side-by-side characteristics. Considering that the phenomenon that describes Bejingan is a conflict between culture and religion, then how can the conflict be balanced and go hand in hand. Then further research needs to be done.